2022
DOI: 10.1111/jftr.12459
|View full text |Cite
|
Sign up to set email alerts
|

Bored of the rings: Methodological and analytic approaches to operationalizing Bronfenbrenner's PPCT model in research practice

Abstract: Bronfenbrenner's ecological (and later bioecological) theory has been a mainstay in the theoretical wheelhouse of developmental and family sciences since its inception in the 1970s. However, few studies accurately operationalize Bronfenbrenner's process‐person‐context‐time (PPCT) research model. The aim of this paper is to provide a practical guide to the design, implementation, and analysis of PPCT research studies. Using recent qualitative and quantitative publications from developmental and family science j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…The model fits were examined via posterior predictive checks (i.e., comparing data generated under each model with observed data), which showed that the models fit well (see Supplementary material). Our observations add to the criticism of interpretations of ecological approaches when failing to accurately operationalize Bronfenbrenner's PPCT research model (Navarro et al, 2022;Tudge et al, 2009Tudge et al, , 2016, particularly failing to consider time (Bronfenbrenner, 2005). It is important to stress that, in sport, the influence of time is measured in years through a continued commitment to training and competition.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The model fits were examined via posterior predictive checks (i.e., comparing data generated under each model with observed data), which showed that the models fit well (see Supplementary material). Our observations add to the criticism of interpretations of ecological approaches when failing to accurately operationalize Bronfenbrenner's PPCT research model (Navarro et al, 2022;Tudge et al, 2009Tudge et al, , 2016, particularly failing to consider time (Bronfenbrenner, 2005). It is important to stress that, in sport, the influence of time is measured in years through a continued commitment to training and competition.…”
Section: Discussionmentioning
confidence: 75%
“…The exposure to deliberate practice is considered a surrogate of process for young athletes. It's important to note that the present study needs to fully comply with the updated PPCT model, as it does not research the proximal processes (Navarro et al, 2022).…”
Section: Bayesian Multilevel Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…This model emphasizes the synergistic relationships between individuals and their environments. Specifically, it places the developing individual, or learner, at the center of a series of nested contextual environments, all of which influence and are influenced by each other and by the individual themselves (Navarro et al, 2022; Rosa & Tudge, 2013). See Figure 1 for a representation of the bioecological model of development.…”
Section: Our Theoretical Frameworkmentioning
confidence: 99%
“…perception, with the intended recipient being more attuned to dysfunction, approval seeking and potential attachment anxiety (Doba et al, 2018;Navarro et al, 2022;Peleg et al, 2023). A child's lack of executive function development may mean they perceive what is being said in an unintended way (Burnett & Blakemore, 2009;Bussey & Bandura, 1999).…”
mentioning
confidence: 99%